2004
DOI: 10.1128/jvi.78.24.13501-13511.2004
|View full text |Cite
|
Sign up to set email alerts
|

Assembly Protein Precursor (pUL80.5 Homolog) of Simian Cytomegalovirus Is Phosphorylated at a Glycogen Synthase Kinase 3 Site and Its Downstream “Priming” Site: Phosphorylation Affects Interactions of Protein with Itself and with Major Capsid Protein

Abstract: Capsid assembly among the herpes-group viruses is coordinated by two related scaffolding proteins. In cytomegalovirus (CMV), the main scaffolding constituent is called the assembly protein precursor (pAP). Like its homologs in other herpesviruses, pAP is modified by proteolytic cleavage and phosphorylation. Cleavage is essential for capsid maturation and production of infectious virus, but the role of phosphorylation is undetermined. As a first step in evaluating the significance of this modification, we have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…1, lanes p62 and p26). This is probably due to posttranslational modifications, such as phosphorylation, which has been reported for other herpesvirus scaffold proteins (5,15).…”
Section: Resultsmentioning
confidence: 99%
“…1, lanes p62 and p26). This is probably due to posttranslational modifications, such as phosphorylation, which has been reported for other herpesvirus scaffold proteins (5,15).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we observed that the C-tail of FGF14 contains a consensus GSK–3 phosphorylation motif ( S/T )XXX(S/T), the first residue in this sequence corresponding to S226. (The phosphorylation motif for GSK–3 contains two serine/threonines: the first, at the P position, corresponds to the site phosphorylated by GSK–3, and the second, at the P + 4 position, corresponds to a priming phosphorylation site that increases the efficiency of GSK–3-dependent phosphorylation (Casaday et al, 2004; St-Denis et al, 2015; ter Haar et al, 2001)). Based on these observations, we conducted an in vitro phosphorylation assay using recombinant GSK–3β with a FGF14 peptide with the sequence KPGVTP S KSTSASAIMNGGK.…”
Section: Resultsmentioning
confidence: 99%
“…The predicted size of the scaffold protein (BdRF1) is 36 kDa, but based on its migration in the gel, it appeared to have a higher molecular mass. One explanation for this could be the observed posttranslational modifications of herpesvirus scaffold proteins (5,16). Accumulation of the protease (BVRF2) was not discernible in these experiments.…”
Section: Resultsmentioning
confidence: 99%